Repensar el mapa de la economía política de la comunicación y la cultura en el contexto de los cambios tecnológicos - Zaragoza Ramírez, Mario Alberto (Pontificia Universidad Católica del Perú, 2023)
Rethinking the theoretical map of the political economy of communication and culture is a pressing task in times where technological changes make visible new ways of understanding cultural consumption, inequality and the significant appropriation of contents. It is not only about information and knowledge technologies, or social media and streaming musical and audiovisual content. The approach and objective of mapping Political Economy, is to include new theoretical frontiers to think new challenges and methodological dimensions that put consumers at the center not only as a buyer or identities imitator, but as an enabler of differences crossed by technology, pollution and excessive consumption in a context of global economies. This contributes to expanding the discussion about the space-time relationship of emerging political, social and cultural processes in the public space.

Reconsiderar y actualizar el mapa teórico de la economía política de la comunicación y la cultura resulta una tarea apremiante en tiempos donde los cambios tecnológicos visibilizan nuevas formas de comprender los consumos culturales, la desigualdad y la apropiación significativa de los contenidos. No se trata sólo de las tecnologías de la información y del conocimiento, de las plataformas electrónicas de interacción social y/o de los contenidos musicales y audiovisuales al alcance por streaming. El planteamiento y objetivo de mapear la economía política, es incluir nuevas fronteras teóricas para pensar nuevos desafíos y dimensiones metodológicas que pongan en el centro a consumidores y consumidoras no sólo como un comprador o imitador de identidades, sino como un posibilitador de diferencias atravesado por la tecnología, la contaminación y el consumo desmedido en un contexto de economías globales. Esto contribuye a ampliar la discusión sobre la relación espacio-tiempo de los procesos políticos, sociales y culturales emergentes que suceden actualmente en el espacio público.
Rethinking the map of the political economy of communication and culture in the context of technological changes
Keywords: Political economy; Communication; Culture; Cultural consumption; Spatiality; Economía política; Comunicación; Cultura; Consumos culturales; Espacialidad; https://purl.org/pe-repo/ocde/ford#5.09.01